APPROXIMATE SOLUTION OF HEAT CONDUCTION THEORY PROBLEM FOR CIRCLE WITH BOUNDARY CONDITIONS OF SECOND SORT - I. N. Meleshko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
It is obtained an approximate solution of the second main boundary problem of heat conduction theory (Neyman’s problem) for Laplasse equation in an individual circle. A uniform estimation of approximate formula error makes it possible to conduct calculations with the given accuracy.